Cytogenetic manifestation of chromosome 11 duplication/amplification in acute myeloid leukemia - Šárová, Iveta; Březinová, Jana; Zemanová, Zuzana; Izáková, Silvia; Lizcová, Libuše; Malinová, Eva; Berková, Adéla; Čermák, Jaroslav; Maaloufová, Jacqueline; Nováková, Ludmila; Michalová, Kyra (Cancer genetics and cytogenetics, 2010)
Gene amplification is a frequent genetic abnormality in solid tumors, and many oncogenes are activated in this way. In acute myeloid leukemia (AML), a frequent target of gene amplification is chromosome 11, particularly chromosome region 11q23, including the MLL (myeloid/lymphoid leukemia) gene. However, the number of other amplicons from the long arm of chromosome 11 has also been described. Duplication/amplification of chromosome 11 was found by cytogenetic methods in 10 of 119 newly diagnosed patients with AML. The amplification was presented as: amplification including only the 5' segment of the MLL gene (1 patient), trisomy 11 (3 patients), partial trisomy 11q (2 patients), isochromosome 11q (1 patient), and multiple amplification of specific regions (3 patients). In two cases, amplification involved parts of not only long arm but also of short arm of the chromosome 11: 11p15 and 11p11.1 to 11p13.
Keywords: dospělí; Female; karyotypizace; Adult; ženské pohlaví; Trisomy; Karyotyping; lidé; Leukemia, Myeloid, Acute; prognóza; Gene Amplification; Male; Aged; duplikace genu; akutní myeloidní leukemie; Prognosis; trizomie; hybridizace in situ fluorescenční; lidé středního věku; Chromosomes, Human, Pair 11; lidské chromozomy, pár 11; senioři; mužské pohlaví; In Situ Hybridization, Fluorescence; amplifikace genu; Middle Aged; Gene Duplication; Humans